Analyzing of Self Esteem, Self Efficacy, and Learning Organization on Employee Performance at PT Bank Republik Indonesia Branch Jemursari Surabaya - Putra Cahyono, Handi; Pompong B. Setiadi; Sri Rahayu (Dinasti Publisher, 2022)
Theory of Self-esteem and self-efficacy in Social Work (including historical reviews of social work alliances inconsistent with self-esteem and self-efficacy theory, emerging power perspectives, and narrative focus (Frankenberger et al. Families develop self-esteem and self-efficacy to pressures of military segregation) (Frankenberger et al., 2014).We see them together in one document. In this case, we want to study the flexibility of banking system factors that have never been done before. Private companies rely mainly on people, and human resources are undoubtedly distinctive. The quality of labor and returns will be the litmus test, that is, turnover high sales force due to low entry and exit b (Rana and Javid, 2019). In this article, we want to empirically examine the concept of flexibility associated with marketers in banking system. We are interested in seeking banking system flexibility for banking system professionals as the banking system factor is the focal point for private companies. It has been noted that the private sector is facing a crisis in the learning skills and competences of field staff - the key business team. They are distinguished by the criteria set for their employment. Anyone with basic training can become a banking system agent and start promoting and selling their own products. (Mahresh, 2014). Private companies need a reliable and strong team to keep improving the company's performance so that it remains competitive and evolving. To have a reliable banking system team, especially in private service companies, it takes rigorous banking system professionals who are smart about providing education to the public, especially potential customers, about the special benefits. Banking system professionals even face obstacles in their work. Results of interviews with researchers with people working in the field of banking system. The interviews revealed that their work was underestimated, leading to them being banned from friendship or family relationships early in their careers as marketers. While the banking system agent has basic needs, social and subjective needs in performing his job. Basic needs, social and subjective needs are factors related to job satisfaction; Stress, career advancement and work environment have emerged as factors for leaving the company.